Anthropometric Characteristics of Top-Class Brazilian Jiu Jitsu Athletes: Role of Fighting Style [Características Antropométricas en Atletas de Jiu Jitsu Brasilero de Alto Nivel: Rol del Estilo de Lucha] - Herrera-Valenzuela, T (Universidad de la Frontera, 2014)
Human performance efficiency and effectiveness in different sports depend to a large extent on the size, weight and proportion of the physique of the athlete. The aim of this study was to identify morphological characteristics of Brazilian Jiu-Jitsu (BJJ) athletes. The sample consisted of 25 highly trained male athletes who were classified according to their fighting style; guard fighter (GF) vs. pass fighter (PF). The athletes were assessed for somatotype, body composition and proportionality. For the whole group of athletes the somatotype was 2.23±0.68, 6.33±1.14, and 1.75±0.87 for endomorph, mesomorph and ectomorph components, respectively. Muscle and adipose tissue percentages were 52.34±2.15% and 19.30±2.51%, respectively. PF were significantly more mesomorph (p< 0.05) and less ectomorph (p< 0.05) than GF. Also, PF had significantly higher phantom Z score for bone mass vs. GF (0.51±0.57 vs. 0.01±0.54; p<0.05), and significantly lower muscle mass- bone mass ratio (4.55±0.31 vs. 4.77±0.56; p<0.05), height (1.71±0.06 vs. 1.77±0.07; p<0.05) and height weight ratio (40.58±1.11 vs. 41.84±1.22). Our results show that morphological characteristics are related to different fighting styles in BJJ athletes. © 2014, Universidad de la Frontera. All rights reserved.